TOTEMISME PADA BUDAYA ASMAT - Rini Maryone (BALAI ARKEOLOGI PAPUA, 2011)
It is clearly seen that totemism is really attached to the ethnic life of the Asmat. This is because the Asmat is always related to ancestor spirits like performing rituals to wish for their bless and protection. The most important thing to communicate to the spirits is the statue of the ancestors. The Asmat uses animal symbols for they hope that the power and goodness of the totem could be transfered and used in their everyday life. Other than the animal and plant design, there are also other type of totem like human and other things which have symbolic meanings for the Asmat.